Inhibiting Roles of Berberine in Gut Movement of Rodents are Related to Activation of the Endogenous Opioid System. (21st January 2013) - Feng, Yajing; Li, Yongyu; Chen, Chunqiu; Lin, Xuhong; Yang, Yuehua; Cai, Haidong; Lv, Zhongwei; Cao, Minghua; Li, Kun; Xu, Jing; Li, Sainan; Jia, Yijun
<x xml:space="preserve">Abstract</x> Although Berberine (BER) is popular in treating gastrointestinal (GI) disorders, its mechanisms are not clear yet. In order to investigate the effects and possible mechanism of BER on GI motility in rodents, we first explored GI motility by recording the myoelectrical activity of jejunum and colon in rats, and upper GI transit with a charcoal marker in mice. Then, the plasma levels of gastrin, motilin, somatostatin and glucagon‐like‐peptide‐1 (Glp‐1) were measured by ELISA or radioimmunoassay (RIA). Furthermore, endogenous opioid‐peptides (β‐endorphin, dynorphin‐A, met‐enkephalin) were detected by RIA after treatment with BER. Our results showed that BER concentration‐dependently inhibited myoelectrical activity and GI transit, which can be antagonized by opioid‐receptor antagonists to different extents. The elevated somatostatin and Glp‐1, and decreased gastrin and motilin in plasma, which were caused by BER application, also could be antagonized by the opioid‐receptor antagonists. Additionally, plasma level of β‐endorphin, but not dynorphin‐A and met‐enkephalin, was increased by applying BER. Taken together, these studies show that BER plays inhibiting roles on GI motility and up‐regulating roles on somatostatin, Glp‐1 and down‐regulating roles on gastrin, motilin. The pharmacological mechanisms of BER on GI motility and plasma levels of GI hormones were discovered to be closely related to endogenous opioid system. Copyright © 2013 John Wiley & Sons, Ltd.